XiMent : Multiplatform cognitive training system based on multimedia technologies and Reminiscence methodology for the population of older adults with mild cognitive impairment. - Simbaña Anrango, Edison Richard (2022)
The application of memory stimulation programs in the aging stage is a term that emphasizes mental health and favors the maintenance or decrease of mild cognitive impairment. Over time, the methodologies used to apply traditional therapeutic exercises have become repetitive, monotonous and tedious therapies in older adults. The rehabilitation process of older adults with cognitive impairment requires multisensory stimulation involving games and multimedia materials that bring dynamism to the treatment, preventing patients from losing interest and motivation during the treatment. Mild cognitive impairment is a geriatric syndrome that affects the cognitive area of attention, learning, thinking and language, which tends to cause depression and feelings of uselessness in the elderly, however, older adults are one of the fundamental pillars of society, and it is essential to provide care and security to this population.